Effect of deep-litter floor and battery cages system on the feed consumption and egg production rate of commercial Layers - Nura El Dikeir Kogoor; Jumma B Jadalla; Mahmoud Fadlelmoula Bakhit; Idris Adam Idris; Mohammed Alhadi Ebrahiem (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
This study was designed to determine the effects of deep litter floor and battery cages housing system on layer feed consumption and egg production rate. Thirty two commercial hybrid layers (hyline) of 10 months production age were randomly selected and distributed equally in four deep litter ground cages, and thirty (hyline) layers were kept in battery cages, which consisted of triple deck cages, provided with automatic nipple watering system and front trough feeders. During the experimental period there were slight changes in live body weight, it was about -0.01 kg in deep litter and about 0.04 kg in battery cages system. Layers housed in deep litter system significantly consumed more feed compared to that kept in battery cages except at first week, and best averages of feed conversion ratios were calculated for layers housed in deep litter than that kept in battery cages, differences were significant for second, third, fourth and fifth weeks of experimental period. Egg production rate were significantly different in layers housed in deep litter system through the production period except the first weeks.